Metaphor-based calques in Croatian mass media - Schmidt Goran; Marinić Ivana (ExELL (Explorations in English Language and Linguistics))
Readers of Croatian daily newspapers and news websites are very frequently faced with Croatian phrases which have been modelled on English templates by literal, word-for-word translation, a phenomenon known as calque. This research shows that even highly proficient Croatian speakers of English as a second language (L2) are sometimes not able to fully understand the calques used in Croatian mass media unless they are familiar with the meaning of their source template in English. The research is done by way of an experiment built in PsychoPy (Pierce, 2007). The implications of this research could be of special interest to persons involved in designing media texts, professional and student translators, as well as to mass media consumers.